Linking performance metrics to financial performance from perspective of agency theory - Pirskanen, Laura Annika (2024)
One of the key tasks of performance management is to implement the company's strategy by directing operations towards goals. However, companies may have challenges defining suitable metrics and understanding their overall impact on the company's goals. The aim of this master's thesis was to investigate the relationship between performance metrics and financial metrics in a production organization, and to identify the connections between these metrics.